Of voyeuristic safari tours and responsible tourism with educational value: Observing moral communication in slum and township tourism in Cape Town and Mumbai - Burgold, Julia; Rolfes, Manfred (DIE ERDE – Journal of the Geographical Society of Berlin, 2013)
Sightseeing in the poorest quarters of southern hemisphere cities has been observed occurring in Cape Town, Rio de Janeiro, Mumbai and many other cities. The increasing global interest in touring poor urban environments is accompanied by a strong morally charged debate; so far, this debate has not been critically addressed. This article avoids asking if slum tourism is good or bad, but instead seeks a second-order observation, i.e. to investigate under what conditions the social praxis of slum tourism is considered as good or bad, by processing information on esteem or disesteem among tourists and tour providers. Special attention is given to any relation between morality and place, and the thesis posited is that the moral charging of slum tourism is dependent on the presence of specific preconceived notions of slums and poverty. This shall be clarified by means of references to two empirical case studies carried out in (1) Cape Town in 2007 and 2008 and (2) Mumbai in 2009.